Occlusion of Epicardial Coronary Arteries by Localized Pericardial Calcification - Yassin, Yassin N. (JACC Case Rep, 2019)
Localized pericardial calcification is a relatively rare finding of often unknown etiology. We present the case of a 68-year-old man who was found to have bulky pericardial calcification, resulting in external compression of epicardial coronary arteries. (Level of Difficulty: Beginner.)